2022
DOI: 10.1108/yc-07-2022-1567
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z’s perceptions and attitudes toward debt: a case study of young consumers in rural Michigan, USA

Abstract: Purpose While there is a large body of research looking at consumers’ perception of debt, much of this previous research focuses on older generations. Less is known about the perceptions and attitudes toward debt of younger consumers, specifically those from Generation Z who are from rural areas in the USA. The purpose of this paper is to identify young rural consumers’ perceptions and attitudes toward debt. Design/methodology/approach This quantitative research used surveys. A well-established scale for mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It appeared that a vulnerable consumer is more susceptible to the message determining that trust. Our results are therefore consistent with the image of the Gen Z consumer reported by Uță (2022), Pradhan et al (2023) or Squires and Ho (2023). According to the authors, Gen Z consumers are more economical and price-sensitive, and compared to older age groups, Gen Z shoppers are less likely to trust companies.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It appeared that a vulnerable consumer is more susceptible to the message determining that trust. Our results are therefore consistent with the image of the Gen Z consumer reported by Uță (2022), Pradhan et al (2023) or Squires and Ho (2023). According to the authors, Gen Z consumers are more economical and price-sensitive, and compared to older age groups, Gen Z shoppers are less likely to trust companies.…”
Section: Resultssupporting
confidence: 92%
“…They are transforming into conscious and responsible buyers who are characterized by concern for the environment natural environment and a decline in confidence in the ethical side of companies' business practices. They are more ethical, sensitive, and careful when it comes to spending money and purchasing decisions (Squires & Ho, 2023). According to McKinsey & Company report (Francis & Hoefel, 2018), Gen Z trust depends on the truth accompanying the product and on the credibility of companies.…”
Section: Consumer Trustmentioning
confidence: 99%
“…They are savings minded, savvy consumers (Entina et al , 2021; Van den Bergh et al , 2020). For instance, Squires and Ho (2023) found that the majority of consumers from Gen Z thinks that using credit is basically wrong and that being in debt is never a good thing. Ameen et al (2022) state that Gen Z is one of the most concerned with physical and mental well‐being and has been associated with low confidence and low self‐esteem.…”
Section: Who Are Gen Z?mentioning
confidence: 99%
“…To further explain Generation Z's perceptions and attitudes toward debt, this study will test the hypothesis that demographic conditions influence Generation Z's perceptions and attitudes toward debt. The demographic conditions and attitudes towards the debt of Generation Z itself have been studied in Michigan, USA by Squires & Ho (2023). This hypothesis needs to be tested in Indonesia because of the differences in culture, demographics, and consumer behavior between America and Indonesia.…”
Section: Introductionmentioning
confidence: 99%